Overview of Examination Results of Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) Levels on Farmers at Padengo Village Sub-District of Dengilo District of Pohuwato - Apriliasari Nento; Rita Amini Warastuti; Sarini Pani (LPPM Universitas Bina Mandiri Gorontalo, 2022)
This research aimed to give an overview about the examination results of Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT) levels of farmers at Padengo Village, sub-district of Dengilo district Pohuwato. This research used a quantitative approach with descriptive analysis. The type of data used was primary data in the form of the results of the research and the secondary data were in the form of data from literature, books and documents. The sampling used simple random sampling technique with a total sample of 29 farmers. The results showed that from the examination of SGOT and SGPT levels, the percentage of normal levels was 69.0% while the percentage of abnormal levels was 31.0%. Based on the length of work of the rice farmers in Padengo Village, for the working period of more than 10 years, the percentage of abnormal SGOT and SGPT levels was 24.1% while the percentage of normal SGOT and SGPT levels was 75.8%; for the working period of less than 5 years, the percentage of abnormal SGOT and SGPT levels was 6.8% but no normal SGOT and SGPT levels were found